Association between scuba diving and neurocognitive disorders in retired military personnel - Runzer-Colmenares, Fernando M. (2018)
Objective: To determine the association between the exposure to scuba diving during military service and the development of neurocognitive disorders in elderly people. Materials and methods: A retrospective analytical study, derived from the database analysis of the study "Fragility and functional dependence in older adults" conducted between 2010 and 2015 on an outpatient basis by the staff of the geriatrics service of the Centro Médico Naval del Perú (Peruvian Naval Medical Center). The chi-square test, p<0.05 and 95 % CI were used to establish said association, and the Poisson model was used as regression model. Results: A total of 1,020 participants were analyzed. Three hundred twenty-two (322 [42.42 %]) participants were between 71 and 80 years of age. Two hundred forty (240 [31.62 %]) had neurocognitive disorders. Factors associated with neurocognitive disorders were: age range between 71 and 80 years of age (PR = 1.69, 95 % CI: 1.12 - 2.54), cerebrovascular disease (PR = 1.48, 95 % CI: 1.01-2.23) and major in scuba diving (PR = 2.36, 95 % CI: 1.64-3.39). A higher military rank was associated with a lower risk of developing neurocognitive disorders (PR = 0.62, 95 % CI: 0.43-0.89). Conclusions: Patients who have practiced scuba diving have a higher risk of developing neurocognitive disorders; however, additional prospective studies are required to confirm this association.